EFL STUDENTS’ ENGAGEMENT IN MULTIMODAL LITERACY THROUGH DIGITAL STORYTELLING - Amatul Olga Firdausya; Indah Purnama Dewi; Hilmansyah Saefullah (PROJECT (Professional Journal of English Education), 2023)
Although many previous studies have examined student or multimodal engagement through digital storytelling. there is still a lack of studies on student engagement in multimodal literacy through digital storytelling. To fill this gap, this case study investigates the involvement of English as a Foreign Language (EFL) students in multimodal literacy through digital storytelling (DST). Taking data from interviews with three junior high school students, it was found that students participated and interacted with other people and the teacher during the activities. In addition, students get motivation in learning English through digital storytelling. Finally, students showed their enjoyment and interest in making digital storytelling activities. Keywords:  Student Engagement; Multimodal literacy; Digital Storytelling